Local perceptions and sociocultural value of Hooded Vultures Necrosyrtes monachus in Burkina Faso, West Africa - DABONE, Clément; OUEDA, Adama; THOMPSON, Lindy J.; ADJAKPA, Boco Jacques; WESSIE, Peter DM (My University, 2022)
Hooded Vultures have suffered from dramatic population declines in recent decades owing to anthropogenic pressures. To properly address this threat, the sociocultural perspectives towards this species should be considered. We examined peoples’ perceptions, knowledge and beliefs on Hooded Vulture’s sociocultural values in Burkina Faso through face-to-face surveys at 20 sites spread across the country. A total of 900 interviews (with 600 householders and 300 butchers) revealed valuable knowledge and an overall positive perception of Hooded Vultures. More than 72% (n = 653) of interviewees (mostly Mossi, Bissa and Gourmatché ethnic groups) regarded Hooded Vultures as important, venerated and sacred birds, and we received no reports of Hooded Vultures attacking livestock—which is all beneficial to their conservation. Conversely, a minority of interviewees (12%, n = 108) believed that Hooded Vultures are harmful, but the reasons provided for this view were insubstantial. Nevertheless, the negative views towards Hooded Vultures should be urgently examined. Furthermore, the vast majority of respondents (84%, n = 753) viewed Hooded Vulture populations as having decreased and the main reasons provided were decreasing food availability, intentional killing using poisoned baits for belief-based use, habitat loss or degradation, and unintentional poisoning. Interestingly, most respondents (84%, n = 760) were acutely aware of the imminence of the Hooded Vulture’s possible extinction and are willing to take conservation measures, suggesting both support and eventual success for conservation actions in this area. The key actions suggested by local communities are valuable for vulture conservation and include severely punishing poachers, supplying safe food for Hooded Vultures, preserving and restoring habitat, and raising awareness of Hooded Vulture conservation.
Keywords: Keywords: anthropogenic threats; conflict and management; cultural use; cultural ecosystem services; local knowledge and perceptions; poisoning; vulture conservation